Successful intelligence and giftedness: an empirical study - Ferrando, Mercedes; Ferrándiz, Carmen; Llor, Laura; Sainz, Marta (Anales de Psicología / Annals of Psychology, 2016)
The aim of our research is to look into the diversity withing gifted and tanlented students. This is important to better undertand their complexity and thus offer a more apropiate educational programs. There are rather few empirical works which attempt to identify high abilities profiles (giftedness and talent) that actually exist beyond the theoretical level. The present work intends to single out the different patterns or profiles resulting from the combination of the successful intelligence abilities (analytical, synthetic and practical), as defined by Stenberg. A total of 431 students from the Region of Murcia participated in this study. These students performed the Aurora Battery tasks (Chart, Grigorenko, & Sternberg, 2008), designed to measure the analytical, practical and creative intelligence. Analytically gifted students (n=27), practically gifted (n=33) and creatively gifted (n= 34) were identifyed, taking as criteria scores equal to or higher than 120 IQ on each intelligence. Different Q-factor analyses were carried out for the three groups of students, in such a way that students were grouped according to their similarities. A total of 10 profiles showing how successful intelligence abilities are combined were obtained, something that has made possible to support the theory put forward by Sternberg (2000): the analytical, practical and creative talent profiles, as well as the resulting combinations, the analytical-practical, analytical-creative, practical-creative profiles, along with the consummate balance talent (high performance in the three types of intelligence).